PEELING BACK THE MASK: THE SHARP EDGE OF HUMOR IN PARO: DREAMS OF PASSION BY NAMITA GOKHALE (International Journal of Food and Nutritional Sciences, 2023)
This research paper delves into the intricate layers of Namita Gokhale’s seminal work, Paro: Dreams of Passion, with a particular focus on the utilization of wit and satire as mechanisms to unveil societal hypocrisies, especially within the context of gender dynamics, power structures, and the cultural identity crises faced by the Indian elite. Through a detailed analysis, the paper elucidates how Gokhale employs humour and irony not merely as narrative embellishments but as potent tools for social commentary and critique. The satirical lens of Paro: Dreams of Passion magnifies the absurdities and contradictions inherent in the adherence to traditional gender roles, revealing the performative nature of societal expectations and the commodification prevalent in male-female relationships among the upper class. The paper explores Gokhale’s incisive portrayal of the Westernized lifestyles and existential voids of the Indian elite, reflecting a profound commentary on the superficial adoption of foreign cultures and the ensuing loss of authentic cultural identity. Through exaggerated characterizations and sharp dialogues, Gokhale’s narrative exposes the viciousness beneath the veneer of sophistication, prompting a re-evaluation of the values and norms that govern elite Indian society.